PENGELOMPOKKAN JUMLAH DESA/KELURAHAN YANG MEMILIKI SARANA KESEHATAN MENURUT PROVINSI DENGAN MENGGUNAKAN METODE K-MEANS CLUSTER - Dwi Retno Sekar Mayangsari; Solikhun Solikhun; Irawan Irawan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Health problems that exist in the community, especially in developing countries such as Indonesia are influenced by two factors, namely physical aspects and non-physical aspects. Physical aspects such as health facilities and treatment of diseases, while the second is non-physical aspects that involve health problems. The construction of health facilities is an effort to fulfill one of the basic rights of the people carried out by the government to provide health facilities that will be used in helping the community to be healthy. So the purpose of this study is to group villages / kelurahan that have health facilities quickly and effectively. Describe the number of villages / kelurahan that have health facilities using the K-Means method, in order to find out whether the constraints faced by the government in grouping villages / kelurahan that have inadequate health facilities based on the provinces in Indonesia, require a long time to group them. It is expected that using this method can produce clustering which is proven to be accurate in the case of the number of villages / kelurahan that have inadequate health facilities based on the provinces in Indonesia.Keywords: Health Facilities, Datamining, K-Means